Optimum Multiobjective Regulator with Variable Gain Matrix Applied to an Industrial Process - Cappelletti, Carlos Alberto; Bernardi, Emanuel; Pipino, Hugo; Adam, Eduardo J. (My University, 2018)
In this paper, it is presented the design and tuning of a robust multi-objective regulator, with variable gain matrix through Linear Matrix Inequalities (LMI). The tuning presented here guarantees for an uncertain model under polytopic representation to satisfy simultaneously multiple objectives such as, asymptotic stability, minimization of the H2-norm, robustness and restrictions imposed on the manipulated variable. Finally, as an application example, this tuning is applied to a Continuous Stirred Tank Reactor (CSTR) typical of the chemical industry.
Keywords: LMI; Optimal Control Multiobjectives; LTV Systems; Variable Gain Matrix